Representasi, Narasi Visual, dan Komodifikasi Tokoh Wayang Gatotkaca-Anoman dalam Mobile Legends dan Honor of Kings - Pulangasih, Sang Pandu Nayenggita (Faculty of Arts and Design, Jakarta Institute of the Arts, 2026)
This article discusses the transformation of the wayang figures Gatotkaca and Anoman in the games Mobile Legends and Honor of Kings. The revised article emphasizes that the presence of wayang in digital games should not only be understood as cultural preservation, but also as a practice of representation and cultural commodification within the digital game industry. This study applies a descriptive-analytical qualitative approach through visual and narrative analysis of character design, visual attributes, hero narrative, skill mechanics, and voice over attached to Gatotkaca and the Anoman skin. The theoretical framework combines Stuart Hall's theory of representation, the concept of cultural commodification, and studies of visual narrative and character design. The findings show that Gatotkaca is represented as a relatively complete main character because his name, role, attributes, and narrative directly refer to Indonesian wayang tradition. In contrast, Anoman in Honor of Kings appears as a skin of Wukong, making local cultural identity function more as a flexible and interchangeable visual layer. These findings reveal a negotiation between cultural preservation, game aesthetics, and digital market logic. Therefore, digital games may become a new space for introducing wayang to younger audiences, while also potentially simplifying its philosophical meanings into visual elements and consumable products.